MEMBANGUN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI DESAIN KOMPETENSI DI SMK NEGERI 2 PROBOLINGGO - Chici Cahyaningrum; Nafisha Arifa Azahra; Wahyu Musrifah Ramadani; Devy Habibi Muhammad (LPPM Institut Nida El-Adabi, 2026)
Islamic Religious Education (PAI) in vocational high schools (SMK) faces significant challenges in balancing cognitive, affective, and psychomotor aspects to align with workforce demands and character development. This study aims to analyze and describe the application of competency design and the formulation of learning objectives to enhance the quality of PAI instruction at SMK Negeri 2 Probolinggo. Employing a qualitative case study approach, data were gathered through participant observation and in-depth interviews, with the PAI teacher serving as a key instrument. The findings indicate that effective competency design is achieved through a systematic processthat involves analyzingstudent needs, determining core and basic competencies that integrate spiritual values with 21st-century skills, and developing comprehensive competency-based assessments. Classroom implementation strategies have shifted from teacher-centered to student-centered models, utilizing approaches such as Contextual Teaching and Learning (CTL), Project-Based Learning (PBL), and differentiated instruction. The study concludes that strengthening teachers' pedagogical, subject-specific, and spiritual competencies is pivotal in shaping the